Emotional intelligence and attentional bias to emotional faces: Evidence of hypersensitivity towards emotion information. (February 2023) - Nicolet-dit-Félix, Maroussia; Gillioz, Christelle; Mortillaro, Marcello; Sander, David; Fiori, Marina
Abstract: It has been proposed that emotional intelligence (EI) functions as a magnifier of emotional experience. This phenomenon, called the "hypersensitivity hypothesis, " predicts that high EI amplifies the emotional aspects of experience (Fiori & Ortony, 2021 ). We tested whether high EI individuals show stronger attention to emotional than neutral expressions with a dot-probe task in which participants ( N = 155) had to report a letter appearing behind an emotional or a neutral face. A significant interaction EI by experimental condition showed an attentional bias towards emotional faces associated with high EI: individuals high on emotion understanding were faster to respond to cues replacing an emotional as compared to a neutral face, an effect that was not found for low-EI individuals. Results support that high EI individuals are particularly reactive to emotion information, confirming the basic assumptions of the hypersensitivity hypothesis. Implications for research on EI are discussed.